THE TRADITION OF CARBITE CANON AS A POTENTIAL TOURISM DESTINATION BASED ON HISTORY OF THE CITY OF PONTIANAK WEST KALIMANTAN - Nunik Esti Utami (International Jurnal of Education Schoolars, 2022)
This study aims to provide information about the Karbit Cannon as a historical-based tourist destination in Pontianak City, West Kalimantan. This research uses descriptive narrative, namely historical writing that has a framework of thinking that is outlined in the form of descriptive narrative, historically methodological research must use historical methods in obtaining data. concrete regarding the data used. the historical method, namely Heuristics, is an activity to collect historical sources, Criticism (verification) examines whether the sources are genuine, both in form and content, Interpretation, to determine the meaning and interrelationships of verified facts, Histography, presentation of the results of the synthesis obtained in the form of a historical story. The result of this research is that the history of the carbide cannon came from the iron cannon used by Sultan Sy. Abdurrahman Alkadrie as a tool to mark the area that will be used as an Islamic kingdom (sultanate) which is part of the history of the city of Pontianak. Karbit cannon tradition is part of the history of the city of Pontianak, a historical-based tourist destination located on the outskirts of the Kapuas river which is held during the month of Ramadan and Eid al-Fitr, which has a historical story where at the time of Sultan Sy. Abdurrahman Alkadrie is the Sultan of the Pontianak Sultanate. three oral stories say that Sy. Abdurahman Alkadrie sounds a cannon to ward off disturbances from supernatural creatures, the Pontianak ghost (kuntilanak), a disturbance that comes from humans in the form of Chinese pirates, fires an iron cannon (Setimbol Cannon) as a tool to mark the territory that will be made an Islamic kingdom (sultanate). After successfully expelling all these disturbances, Sultan Sy. Abdurrahman Alkadrie was finally able to resume building the sultanate which is now named Pontianak City. Karbit Cannon Festival Due to the uniqueness of this cannon, the Pontianak Government took the initiative to promote it as a cultural and historical tourism object by making a Cannon Festival on the banks of the Kapuas river